Do Ethics and Controls Prevent Fraud? Investigating Accounting Malpractice Drivers in Yogyakarta’s Government Agencies - Khoirunisa, Kharisa; Ghafira Zanbaina (Jurnal Magister Ekonomi Syariah, 2025)
This study explores the impact of religiosity, internal control, and compensation appropriateness on accounting fraud within government institutions in the Special Region of Yogyakarta (DIY), focusing on the Regional Financial and Asset Management Agency (BPKAD) and related offices. Using a quantitative approach, data were collected from 90 finance personnel through structured questionnaires and analyzed via multiple linear regression. The results indicate that both religiosity and internal control have a significant negative effect on accounting fraud, suggesting that individuals with strong religious values and organizations with robust internal control systems are less likely to engage in fraudulent behavior. In contrast, compensation appropriateness showed no significant impact on accounting fraud, indicating that fair compensation alone does not deter unethical actions. These findings align with the fraud triangle theory, where religiosity and internal controls function as moral and procedural deterrents to fraud, while compensation alone does not effectively address the broader systemic and ethical issues. The study highlights the importance of integrating ethical and religious values into organizational culture, along with strengthening internal controls, to combat fraud in the public sector. This research contributes valuable insights for policy and practice in public financial management and offers a foundation for further investigation into fraud prevention strategies in government institutions.